2016
DOI: 10.1177/0091217416680839
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of major depression among Nigerian adults with sickle cell disease

Abstract: Objective To ascertain the current and lifetime prevalence of depression among adults with sickle cell disease and identify relevant socio-demographic and clinical correlates. Method A cross-sectional study of 205 stable adult out-patient attendees at a treatment center in southern Nigeria between April and September, 2014. A socio-demographic questionnaire, the depression module of Mini International Neuropsychiatric Interview, and the eight-item Morisky Medication Adherence Scale were administered. Categoric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 25 publications
3
29
1
1
Order By: Relevance
“…As with most chronic diseases, the prevalence of depressive symptoms is evident, 11 , 17 - 19 however, it is high in our study compared to that reported in most of the previous studies. 8 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with most chronic diseases, the prevalence of depressive symptoms is evident, 11 , 17 - 19 however, it is high in our study compared to that reported in most of the previous studies. 8 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…The current study did not show significant association between depressive symptoms and socio-demographic factors which was the second goal of the study, in contrast to other studies which found to be significant among patients with low income, poor social support, less than high school education and low family income, and unemployed. 8 , 12 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Most studies found no association with other demographic variables or education (Jewett, Razykov, Hudson, Baron, & Thombs, 2013;Manti et al, 2016;Roos et al, 2016;Wei et al, 2016). Contrarily, two studies (Nonnenmacher et al, 2013;Raji, Lawani, & James, 2016) found that depression was associated with lower education, unemployment, and low income.…”
Section: Patient-related Featuresmentioning
confidence: 99%
“…The majority of studies examining the relation between clinical symptoms of the rare diseases and psychopathology found no associations (Baubet et al, 2011;Cardoso et al, 2004;Chen et al, 2015;Gordon-Smith et al, 2010;Gündel et al, 2001;Naarding, Janzing, Eling, van der Werf, & Kremer, 2009;van Os et al, 2007;Wei et al, 2016) or only with single symptoms (Baubet et al, 2011;Jewett et al, 2013;Raznahan et al, 2006). Three studies reported an association between pain and depression or anxiety (Baubet et al, 2011;Rabkin et al, 2000;Raji et al, 2016). Illness duration showed no association with depression or anxiety in six studies (Gündel et al, 2001;Henningsen & Meinck, 2003;Krogias et al, 2011;Lu et al, 2017;Nonnenmacher et al, 2013;Wei et al, 2016), two studies found higher psychopathology early in the disease course or early after diagnosis for anxiety (Moore et al, 2016) and affective disorders (Roos et al, 2016).…”
Section: Disease-related and Clinical Featuresmentioning
confidence: 99%
“…No entanto, a depressão na doença falciforme também resulta do sofrimento causado por atitudes discriminatórias de pessoas que reduzem os adoecidos a estereótipos, destinando-lhes tratamentos descorteses e desiguais, principalmente nas unidades de emergência, imputando-lhes mais padecimento do que a própria doença e os desanimando a buscar ajuda, quando necessária, devido à antecipação do estigma. (21,22) Tendo sua situação de saúde mental comprometida e intensificada pelo processo de estigmatização, o padecimento gerado pela doença crônica conduz os homens a uma rotina rígida de cuidados, que os recorda da necessidade de estar vigilante para com seu corpo e sua saúde. Nesse sentido, os homens percebem que contrariam os modelos de masculinidade hegemônicos ainda vigentes no contexto atual brasileiro, na medida em que atitudes de cuidado se opõe à idealizada imagem do homem "invulnerável".…”
Section: Discussionunclassified